Case Report: Multiple intra-abdominal lymph node abscesses due to Staphylococcus aureus in a cat - Tamura, Kei; Kushida, Kazuya; Iwanaga, Tomoko; Fukushima, Ryuji; Ohmori, Keitaro (Frontiers in Veterinary Science, 2025)
Intra-abdominal lymph node abscesses (LAs) are rare in cats and have previously been reported only in the mesenteric lymph nodes, caused by Escherichia coli or Listeria monocytogenes. The full spectrum of causative agents and the underlying pathogenesis remain poorly understood. A 4-year-old spayed indoor cat presented with a one-week history of fever and anorexia. Laboratory tests revealed marked neutrophilia, eosinophilia, and an elevated feline serum amyloid A level. Computed tomography identified cyst-like masses in the medial iliac and hepatic lymph nodes. Cytological analysis showed infiltration by neutrophils and macrophages without neoplastic cells. Gram-positive cocci were observed, and Staphylococcus aureus was isolated from the abscesses. Based on antimicrobial susceptibility testing, amoxicillin was selected as the treatment. Administration of amoxicillin led to clinical improvement and normalization of hematological abnormalities. Antibiotic therapy was continued for approximately 6 months, after which no recurrence was observed. The cat remained in good health at 689 days after the initial presentation. This is the first reported case of multiple intra-abdominal LAs caused by S. aureus in a cat. The case highlights the pathogenic potential of this commensal bacterium and underscores the importance of long-term, susceptibility-guided antibiotic therapy in achieving complete resolution.